Related-Party Transactions and Audit Fees - Fortuna Oktavia Perwita; Iman Harymawan (Universitas Negeri Malang, 2021)
This research aims to analyze the association between the related-party transactions and audit fees. This study used 781 observations listed on the Indonesia Stock Exchange from 2010 to 2017. The analysis technique used in this research was the Ordinary Least Square Regression analysis model processed with STATA 14.0 software. This study found that related-party transactions are positively and significantly related to audit fees. The result indicated that the related-party transactions increase audit fees paid by companies. It also investigated the moderating effect of industry specialty auditors. This indicated that auditor specialization strengthened the relationship between the related-party transactions and audit fees. The market share proxy was used to measure industry specialization. However, this proxy still has disadvantages as it can generate different market shares. This study found that related-party transactions increased audit fees. The results of this study can be used as consideration in making decisions for related parties.